Structural investigation of alcohol oxidase from Meyerozyma guilliermondii and the use of its promoter for recombinant protein expression - Mahyon, Nur Iznida (2017)
Alcohol oxidase promoter (pAOX1) is a tightly regulated methanol inducible promoter in methylotrophic yeasts. The use of methanol is a vital factor in pAOX1 regulation. Locally isolated yeast strain SO (with partial characterisation) has been developed to be an expression host using pAOX1 (origin: Pichia pastoris). It demonstrated the capability to express recombinant bacterial lipase faster than P. pastoris expression system with minimal methanol induction from previous study. The pAOX1 of strain SO shared 100% similarity of pAOX1 in P. pastoris, but its AOX gene has not been identified yet. Therefore, the two main objectives of this project are to investigate the type of AOX gene in strain SO with its function and to use its pAOX1 in the expression of recombinant proteins (other than lipase). In addition, further characterisation (morphological and biochemical) were done to characterise this strain. The microscopy analysis (using scanning and transmission electron microscopy) and carbon assimilation results confirmed that strain SO was a Meyerozyma guilliermondii. Hidden Markov Model (HMM) analysis was performed to identify AOX protein from reference proteome (M. guilliermondii ATCC6260). The protein was identified as a long chain alcohol oxidase (LCAO). Then, the full of LCAO gene was amplified from M. guilliermondii strain SO genome via PCR using primer walking technique. Initial bioinformatics (structural) analysis indicated that the open reading frame (ORF) of the LCAO in this strain (referred as MgFAO1) composed of FAD-binding domain (the most conserved domain in the AOX protein). Based on the phylogenetics analysis, the MgFAO1 was clustered with other LCAOs. The function of MgFAO1 was identified by predicting the three- dimensional (3D) structure using YASARA and validated by PROCHECK, ERRAT and Verify3D. Docking analysis showed that MgFAO1 has corresponded to the long chain alcohol substrate (1-dodecanol). To achieve the second objective, two enzymes (diamine oxidase and W200R protease) were cloned into pPICZαB (driven by pAOX1) and transformed into M. guilliermondii strain SO via electroporation method. The results showed that, all the recombinant proteins were successfully expressed in both conditions (with and without methanol). This result suggested that the pAOX1 might use the MgFAO1 to facilitate the recombinant proteins expression in this strain without methanol induction as it favoured 1-dodecanol than methanol. As a conclusion, the structure of AOX in M. guilliermondii strain SO was investigated for its function and different recombinant proteins were successfully expressed using its pAOX1 in the absence of methanol. This newly developed yeast system can be used for recombinant protein production particularly for food product since expression can be done without methanol induction.